Hubungan Pengetahuan dan Sikap Dengan Perilaku Pencegahan Demam Tifoid Pada Penjamah Makanan - Tyagita Widya Sari; Sri Wahyuni (Sistem Informasi, 2021)
Typhoid fever is a disease that attacks the digestive tract, caused by the bacteria Salmonella typhi. This disease can occur due to low personal hygiene, slum environmental sanitation, and habit of snacking carelessly. Typhoid fever prevention behavior in food handlers is needed to reduce the incidence of typhoid fever, where this behavior is influenced by the knowledge and attitudes of the food handlers about the prevention of typhoid fever. The purpose of this research was to determine the correlation between knowledge and attitudes about typhoid fever prevention with typhoid fever prevention behavior in food handlers in Air Hitam Sub District Payung Sekaki District Pekanbaru City. The research method used an analytic survey with a cross sectional approach. The sampling technique used accidental sampling with a sample size of 30 respondents. The data analysis used the Spearman correlation test, because the data were not normally distributed. There was a relationship between knowledge about typhoid fever prevention and typhoid fever prevention behaviors among food handlers with moderate correlation strength and positive correlation direction (p-value = 0.000; r = 0.555). There was also a relationship between attitudes about typhoid fever prevention and typhoid fever prevention behaviors among food handlers with strong correlation strength and positive correlation direction (p-value = 0.000; r = 0.674). The conclusion of this research was knowledge and attitude about typhoid fever prevention correlate with typhoid fever prevention behaviors among food handlers in Air Hitam Sub District Payung Sekaki District Pekanbaru City.